Nutrient Availability and Atmospheric CO(2) Partial Pressure Modulate the Effects of Nutrient Heterogeneity on the Size Structure of Populations in Grassland Species - MAESTRE, FERNANDO T. (Oxford University Press, 2006)
• Background and Aims Size-asymmetric competition occurs when larger plants have a disproportionate advantage in competition with smaller plants. It has been hypothesized that nutrient heterogeneity may promote it. Experiments testing this hypothesis are inconclusive, and in most cases have evaluated the effects of nutrient heterogeneity separately from other environmental factors. The aim of this study was to test, using populations of Lolium perenne, Plantago lanceolata and Holcus lanatus, two hypotheses: (a) nutrient heterogeneity promotes size-asymmetric competition; and (b) nutrient heterogeneity interacts with both atmospheric CO(2) partial pressure (P(CO(2))) and nutrient availability to determine the magnitude of this response. • Methods Microcosms consisting of monocultures of the three species were grown for 90 d in a factorial experiment with the following treatments: P(CO(2)) (37·5 and 70 Pa) and nutrient availability (NA; 40 and 120  mg of N added as organic material) combined with different spatial distribution of the organic material (NH; homogeneous and heterogeneous). Differences in the size of individual plants within populations (size inequality) were quantified using the coefficient of variation of individual above-ground biomass and the combined biomass of the two largest individuals in each microcosm. Increases in size inequality were associated with size-asymmetric competition. • Key Results Size inequality increased when the nutrients were heterogeneously supplied in the three species. The effects of NH on this response were more pronounced under high nutrient supply in both Plantago and Holcus (significant NA × NH interactions) and under elevated P(CO(2)) in Plantago (significant P(CO2) × NA × NH interaction). No significant two- and three-way interactions were found for Lolium. • Conclusions Our first hypothesis was supported by our results, as nutrient heterogeneity promoted size-asymmetric competition in the three species evaluated. Nutrient supply and P(CO(2)) modified the magnitude of this effect in Plantago and Holcus, but not in Lolium. Thus, our second hypothesis was partially supported.